2008
DOI: 10.1002/prot.22178
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants of species‐selective substrate recognition in human and Drosophila serotonin transporters revealed through computational docking studies

Abstract: To identify potential determinants of substrate selectivity in serotonin (5-HT) transporters (SERT), models of human and Drosophila serotonin transporters (hSERT, dSERT) were built based on the leucine transporter (LeuT Aa ) structure reported by Yamashita et al. (Nature 2005;437:215-223), PBDID 2A65. Although the overall amino acid identity between SERTs and the LeuT Aa is only 17%, it increases to above 50% in the first shell of the putative 5-HT binding site, allowing de novo computational docking of trypta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
76
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 44 publications
13
76
0
Order By: Relevance
“…We suspect the inability of the SERT M172 substitution to reduce paroxetine potency reflects a distinct orientation of paroxetine compared with other SSRIs in the 5-HT binding pocket, particularly given that high-affinity SSRI recognition at SERT can be strongly influenced by relatively small changes in transporter structure (34). SERT M172 cell lines should be useful in further exploring the physical basis of interactions of different antidepressants in vitro (26), whereas the SERT M172 mice should help define the requirements for SERT and 5-HT signaling in the in vivo actions of antidepressants and cocaine. Although significant evidence supports a primary role for the 5-HT transporter in the reinforcing properties of psychostimulants (35)(36)(37), SERT blockade also appears to contribute to reinforcement (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suspect the inability of the SERT M172 substitution to reduce paroxetine potency reflects a distinct orientation of paroxetine compared with other SSRIs in the 5-HT binding pocket, particularly given that high-affinity SSRI recognition at SERT can be strongly influenced by relatively small changes in transporter structure (34). SERT M172 cell lines should be useful in further exploring the physical basis of interactions of different antidepressants in vitro (26), whereas the SERT M172 mice should help define the requirements for SERT and 5-HT signaling in the in vivo actions of antidepressants and cocaine. Although significant evidence supports a primary role for the 5-HT transporter in the reinforcing properties of psychostimulants (35)(36)(37), SERT blockade also appears to contribute to reinforcement (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Based on hydrophobicity assessments and high-resolution crystal structures of the SLC6 family member LeuT Aa , SERT is proposed to contain 12 transmembrane domains (TMs), four of which-TMs 1, 3, 6, and 8-provide the key residues for ion and substrate recognition (24)(25)(26)(27). By using the pharmacological differences displayed by human and Drosophila melanogaster SERTs (hSERT and dSERT), we identified variation at a single residue in TM3 (I172 in human and mouse, M167 in fly) proximal to the proposed binding site for 5-HT (28).…”
mentioning
confidence: 99%
“…In LeuT Aa , TMs 1, 3, 6, and 8 form the leucine binding pocket. Biochemical analyses and homology modeling of SERT proteins predict a similar binding pocket for 5-HT (32)(33)(34)(35)(36). Consistent with these models, pre-structure studies identified residues in hSERT TMs 1 and 3 that confer high affinity interactions and ligand selectivity to substrates and antagonists.…”
mentioning
confidence: 57%
“…Impact of Na ϩ on MTSET Inactivation-The LeuT Aa crystal structure and hSERT homology models derived from it predict that TM6 is involved in the coordination of a sodium ion (27,(32)(33)(34)36). Interestingly, replacement of sodium with NMDG in the MTS incubation buffer resulted in protection of three TM6 Cys mutants and exposure of a single mutant (Fig.…”
Section: G338c Appears To Stabilize An Open Conformation Of Hsert-mentioning
confidence: 98%
See 1 more Smart Citation